Plan estratégico para el mejoramiento del servicio de transporte de la cooperativa de pasajeros en taxis "Gregorio Valencia", periodo 2014-2017 - Cañizares Angueta, Angela (2015)
This research project entitled "Strategic Plan for the Improvement Service Cooperative Passenger Transportation Taxis" Gregorio Valencia ", period 2014- 2017" was conducted with the aim of improving the shuttle passengers in taxis cooperative Gregorio Valencia, Valencia Canton, based on the need for a strategic plan to establish a planning, coordination, monitoring and implementation of activities adding value to the service, among the most relevant results can cite the following: The cooperative Gregorio Valencia, regarding its creation and legal constitution, has eight years of institutional life, therefore concludes that it is a strength for it by his experience as a pioneering activity in the canton taxismo Valencia. According to the response of the Manager of the Cooperative, this if you have a strategic plan, but also, it is determined that the Plan should be aligned to the proposal as a Strategic Plan, since a structure and the technical elements is defined to be considered for development of the activity of the institution and its cooperative members. The conclusions from the interview technique applied to the manager of the cooperative Gregorio Valencia, states that if you have a vision and institutional mission, however, it is recommended socialize with the Talent of the institution for its implementation, on what you want to be; and how to achieve it Finally it is concluded that there is a conviction that the implementation of an institutional strategic plan will improve the shuttle passengers in taxis with added value in quality and warmth for customers and users of the cooperative Gregorio Valencia, Cantón Valencia.